The Relationship between High-Intensity Physical Activity and Traumatic Dental Injury among Young Adults in South Korea - Ji-Young Son; Dong-Hun Han (International Journal of Dentistry)
Background and Aim. High-intensity physical activities have become increasingly popular in recent times. However, they are associated with an elevated risk of unintentional traumatic dental injury. Therefore, the aim of this study is to evaluate the correlation between high-intensity physical activity and traumatic dental injury due to exercise in young adults. Materials and Methods. This study analyzed data collected from the 5th National Health and Nutrition Examination Survey (KNHANES V:2010−2012). The total number of participants in the 5th KNAHANES was 5,383 young adults aged 19–39 years, selected from 25,534 participants. Logistic regression analysis was performed using socioeconomic status (sex, age, education level, and income), physical activity intensity (vigorous and moderate), frequency of vigorous and moderate physical activity (days per week), and traumatic dental injuries due to exercise. Results. A total of 5,383 participants were included in the analysis. High-intensity exercisers had a statistically different association with traumatic dental injuries due to exercise. In all models, high-intensity exercisers had more traumatic dental injuries than moderate-intensity exercisers, and participants who exercised vigorously 4 or more days per week had a significantly higher prevalence experience of traumatic dental injuries. Among adults in their 20s, men, college attendees, and those with higher incomes, the prevalence of exercising vigorously 4 or more days per week was higher. Conclusions. Among young adults, a higher frequency of high-intensity physical activity was associated with a higher prevalence experience of traumatic tooth injury due to exercise compared with no physical activity.